The The effect of adoption of frequent harvesting, pruning, sanitation and fertilization on increasing cocoa production (case study: Tapango District, Polewali Mandar Regency) - Khaeratih, Rahma; Karim, Ikawati; Nurlaela (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2021)
The lack of consistency of farmers in implementing good agriculture practice has led to the adoption of innovations o frequent Harvesting, Pruning, Sanitation and Fertilization are important to maintain the quality of the cocoa beans produced. This research was carried out in one of the cocoa centers in West Sulawesi, namely in the Village of Tapango, Polewali Mandar Regency with the aim of knowing the effect of the adoption of frequent harvesting, pruning, sanitation and fertilization on increasing cocoa production. This type of research is descriptive quantitative in which the determination of the sample is carried out by the Slovin method in order to obtain 65 cocoa farmers who apply the adoption of Frequent Harvesting, Pruning, Sanitation and Fertilization. The data analysis used in this research is simple regression analysis and the coefficient of determination. The results of the data analysis showed that the innovation adoption of Frequent Harvesting, Pruning, Sanitation and Fertilization to the increase in cocoa production was very influential with a percentage level or determination coefficient (R2) of 96.8 percent. In addition, the results of the study also showed that through the adoption of innovation, the production of cocoa plants increased by 3.17 tons per hectare. Therefore, it is hoped that the implementation of the innovation adoption of Frequent Harvesting, Pruning, Sanitation and Fertilization to be continued to implement by cocoa farmers in a sustainable manner in Polewali Mandar.